A Modest Proposal. (June 2014) - Oldenburg, Mark
Abstract The language of "consecration" to describe what the presider does at Holy Communion seems to have many more drawbacks than advantages. Based on a misunderstanding of the Institution Narratives, it nurtures an understanding of the Sacrament centered on the presider and the elements, while marginalizing the assembly. It leads to the unthinking adoption of practices with significant theological hazards. In every way, "presiding" is to be preferred.